The Manifestation of White Supremacy in The Track to Bralgu by B. Wongar (1978) - Andrian, Fadel; Anwar, Desvalini (Universitas Negeri Padang, 2023)
This thesis focuses on The Track to Bralgu, an anthology of Aboriginal stories written by Bozic Wongar. The novel concerns with the domination, exploitation, and discrimination of the Aborigines. The novel emphasizes on the superiority of the Whites. The aim of this study is to gain the understanding on how white supremacy is manifested in The Track to Bralgu by B. Wongar and how racial discrimination or racism is being implemented as the manifestation of white supremacy in The Track to Bralgu by B. Wongar. The objectives of the study are: first, to explain the manifestation of white supremacy in The Track to Bralgu by B. Wongar; second, to analyze racial discrimination or racism as the manifestation of white supremacy in The Track to Bralgu by B. Wongar. The method that was conducted in the study is the qualitative method. In conducting the analysis, postcolonialism approach was applied. By applying postcolonialism approach, the writer is able to understand the motive of the Whites doings over the Aborigines. The result of the study shows in The Track to Bralgu, the manifestation of white supremacy is depicted through the racial discrimination or racism of the Whites towards the Aborigines. The implementation of the manifestation of white supremacy in The Track to Bralgu is marginalization and segregation.